2008
DOI: 10.1111/j.1525-1314.2008.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐density nitrogen inclusions in barite from a giant siderite vein: implications for Alpine evolution of the Variscan basement of Western Carpathians, Slovakia

Abstract: Contrasting compositions and densities of fluid inclusions were revealed in siderite-barite intergrowths of the Drozˇdiak polymetallic vein hosted in Variscan basement of the Gemeric unit (Central European Carpathians). Primary two-phase aqueous inclusions in siderite homogenized between 101 and 165°C, total salinity ranged between 18 and 27 wt%, and CaCl 2 ⁄ (NaCl + CaCl 2 ) weight ratios were fixed at 0.1-0.3. By contrast, mono-and two-phase aqueous inclusions in barite exhibited total salinities between 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 47 publications
6
29
0
Order By: Relevance
“…The foliationparallel orientation of veins was interpreted as reflecting an arcuate deformation front during the Early-Cretaceous thrusting (Lexa et al 2003;Hurai et al 2008a). This model is supported by superdense CO 2 inclusions in quartz-stibnite veins (Urban et al 2006) and very high-density N 2 inclusions in barite from siderite veins (Hurai et al 2008b), which indicated a 14-15 km burial under imbricate stack of nappes thrusted over the Gemeric basement (Hurai et al 2010).…”
Section: Introductionmentioning
confidence: 96%
“…The foliationparallel orientation of veins was interpreted as reflecting an arcuate deformation front during the Early-Cretaceous thrusting (Lexa et al 2003;Hurai et al 2008a). This model is supported by superdense CO 2 inclusions in quartz-stibnite veins (Urban et al 2006) and very high-density N 2 inclusions in barite from siderite veins (Hurai et al 2008b), which indicated a 14-15 km burial under imbricate stack of nappes thrusted over the Gemeric basement (Hurai et al 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Experimental studies over recent years have advanced understanding of the microstructural changes induced by variations in hydrostatic confining pressure (Gratier and Jenatton 1984;Pêcher and Boullier 1984;Boullier et al 1989;Sterner and Bodnar 1989;Vityk and Bodnar 1995;Vasyukova and Fonarev 2006). Recognition of the characteristic microstructures in natural samples has permitted reconstruction of the history of pressure evolution in the host rocks (Vityk et al 1994(Vityk et al , 1996Ayllon et al 2003;Hurai et al 2008;Mukherjee and Sachan 2009;Stöckhert et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…All the siderite‐hosted inclusions contain aqueous liquid with a 5–15 vol.% of vapour phase (Varček 1968; Borisenko et al. 1984; Hurai et al. 1998, 2002, 2008).…”
Section: Fluid Inclusionsmentioning
confidence: 99%
“…Hurai et al. (2002, 2008) argued that high fluid pressures indicated by oxygen isotopes and fluid inclusions in siderite and barite from the Droždiak vein in the northern part of the Gemeric unit were much greater than a lithostatic load of Permo‐Triassic autochthonous sedimentary cover.…”
Section: Introductionmentioning
confidence: 99%